Perancangan Desain Antarmuka Visual Sistem Antrian Pasien Puskesmas - Khoiri, Syarif Aminul; Zubairi, Ach; Samad, Abdus; Adiman, Muhammad Fauzen; Jazil, Afwil (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2026)
Hospital queues are often chaotic and confusing for patients. Many patients do not know when their turn is or which room to go to. This problem makes waiting times feel longer and stressful for visitors. Therefore, a good visual interface for the queue system is needed to give clear information to everyone. The purpose of this study is to design a user-friendly visual interface for a hospital patient queue system. The method used in this research is simple observation of the current queue flow and creating a design prototype using a computer application. The design process focuses on making the display simple, clean, and easy to read for people of all ages. The results of this study are interface designs for the ticket-taking machine (kiosk) and the main queue display monitor. The design uses large fonts and clear color differences to show the queue number, polyclinic destination, and doctor's name. In conclusion, this interface design helps patients understand the queue flow better. It creates a more orderly and comfortable environment in the hospital waiting room.